interactivity, JASP, programming education, research, statistics - Sobkin V.S.; Lykova T.A.; Sobkina A.V. (Психолого-педагогические исследования)
The article deals with the peculiarities of relations with teachers among students with preserved health and students with disabilities. It is assumed that students with disabilities and students with preserved health have specific features in their relationships with teachers. Sample: 167 students, 98 of them – with good health and 67-with disabilities (hearing, vision, etc.). The study was conducted on the basis of the RSSAI with students of all faculties (theater, music, fine arts). Methodology: the author's questionnaire on the study of various aspects of the attitude to education (professional plans, socio-psychological well-being, motivation of training, attitude to the content of education, socio-psychological relations within the university with teachers and other students, value orientations in the field of art culture, etc.). It is shown that when there are conflicts with teachers, students with preserved health do not transfer them to the attitude to the academic subject, while students with disabilities conflict with the teacher provokes a negative attitude to the course. It was revealed that among students with disabilities, almost one in ten believes that problems in understanding the educational material are due to the peculiarities of their health, with age the share of such responses increases. It was found that among students with disabilities a higher proportion of those who seek informal communication with teachers, which confirms the importance of higher education as an institution of socialization and a source of experience of social interaction.